2015
DOI: 10.1161/strokeaha.114.007581
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Selective Neuronal Loss, Impaired Behavior, and Normal Magnetic Resonance Imaging in a New Rat Model of True Transient Ischemic Attacks

Abstract: M ost transient ischemic attacks (TIAs) are secondary to transient arterial occlusion from upstream blood clot. According to their new tissue-based definition, TIAs are characterized both clinically by focal neurological symptoms of ischemic origin lasting <24 hours and radiologically by a lack of topographically congruent changes on diffusion-weighted imaging (DWI) or FLAIR magnetic resonance imaging (MRI) performed within 2 weeks of the clinical event.1 Normal imaging in true TIAs, which account for 20% to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…This observation first suggests that despite no evidence of macroscopic damage, TIA actually induces tissue sequelae, consistent with previous post-mortem histological findings (Ejaz et al, 2015(Ejaz et al, , 2016, but that our MRI modality noninvasively unmasks. Second, in the clinical setting, this time window gives a reasonable opportunity to process imaging, and to identify patients eligible for prevention.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This observation first suggests that despite no evidence of macroscopic damage, TIA actually induces tissue sequelae, consistent with previous post-mortem histological findings (Ejaz et al, 2015(Ejaz et al, , 2016, but that our MRI modality noninvasively unmasks. Second, in the clinical setting, this time window gives a reasonable opportunity to process imaging, and to identify patients eligible for prevention.…”
Section: Discussionsupporting
confidence: 88%
“…Here, we first implemented and optimized previous models to establish a preclinical mouse model of TIA complying with the tissue-based definition. This model combines the advantages of these previous models (Fieschi et al, 1975;Arsava et al, 2009;Pedrono et al, 2010;Morancho et al, 2012;Ejaz et al, 2015): it is relatively non-invasive, robust, reproducible, easy to control, and preserves the dura. The main achievement with this model is the supply of an MRI-based objective evidence of TIA.…”
Section: Discussionmentioning
confidence: 91%
“…44 However, the site of SNL is known to dictate the behavioral effects of stroke, with striatal SNL seemingly having less clear sensorimotor effects than cortical SNL. 16,45 Severe striatal SNL has, however, been reported to impair performance on sophisticated cognitive tests, 46,47 but these were not implemented in the present study.…”
Section: Behaviormentioning
confidence: 78%
“…It has been reported that activated microglia increased proinflammatory cytokines, including TNF-α, IL-1ÎČ and IL-6 in the ischemic stroke, which exacerbates the cortical selective neuronal loss and long-lasting sensorimotor behavior deficits [7][8]17,[55][56]. Long-term neuroinflammation is strongly induced gray-and white-matter damage, which contributes to long-term sensorimotor impairment [57].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the cerebral I/R characterized by microglia-mediated neuroinflammation is involved in the brain edema, blood-brain barrier damage and neuronal loss or degeneration, which cause long-lasting neurological and sensorimotor deficits [17][18]. Therefore, attenuating of neuroinflammation effectively protects brain, which is considered as an important therapeutic strategy for improving neurological function after ischemic stroke [19][20].…”
Section: Introductionmentioning
confidence: 99%